2001
DOI: 10.1021/bi0107593
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Fingers and Thiol−Disulfide Oxidoreductase Activities of Chaperone DnaJ

Abstract: Chaperone DnaJ is a homodimer with each subunit containing 10 cysteine residues and two Zn(II) ions, which have been identified to form two zinc fingers, C(144)DVC(147)Zn(II)C(197)NKC(200) (Zn1) and C(161)PTC(164)Zn(II)C(183)PHC(186) (Zn2), with C(265) and C(323) in reduced form. Guanidine hydrochloride at 6.4 M destroys only Zn1, which does not reform after refolding. p-Hydroxymercuriphenylsulfonate acid, but not ethylenediaminetetraacetic acid (EDTA) even at high concentrations, can remove two Zn(II) ions fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 35 publications
2
46
0
2
Order By: Relevance
“…This agreed well with the modular character of DnaJ proteins and suggested that the 79 amino acid cysteine-rich domain is also an autonomous folding unit in the full-length protein. The results were also in good agreement with studies using metalfree full-length DnaJ, which demonstrated that even in the absence of any zinc coordination, DnaJ undergoes probably only local structural changes (36). These local changes most likely include the partial unfolding of the zinc binding region, because in the isolated cysteine-rich domain, absence of zinc has been shown to cause the unfolding of the ␤-hairpin structure (21).…”
Section: Discussionsupporting
confidence: 79%
“…This agreed well with the modular character of DnaJ proteins and suggested that the 79 amino acid cysteine-rich domain is also an autonomous folding unit in the full-length protein. The results were also in good agreement with studies using metalfree full-length DnaJ, which demonstrated that even in the absence of any zinc coordination, DnaJ undergoes probably only local structural changes (36). These local changes most likely include the partial unfolding of the zinc binding region, because in the isolated cysteine-rich domain, absence of zinc has been shown to cause the unfolding of the ␤-hairpin structure (21).…”
Section: Discussionsupporting
confidence: 79%
“…Zn2 is important for the enzymatic activity of DnaJ (Tang and Wang, 2001), such as reduction of insulin disulfides and protein disulfide formation (e.g., oxidative renaturation of reduced RNase) (de Crouy-Chanel et al, 1995). To analyze the catalytic properties of CYO1, we tried to express full-length CYO1 in E. coli, but it was insoluble under all E. coli growth/detergent conditions we tried.…”
Section: Cyo1 Has Protein Zn-dependent Disulfide Isomerase Activitymentioning
confidence: 99%
“…When these bonds are broken, the free B chain is insoluble and precipitates, increasing absorbance at 650 nm. DnaJ in E. coli catalyzes the DTT-dependent reduction of insulin (de Crouy-Chanel et al, 1995;Tang and Wang, 2001;Shi et al, 2005). We measured the reduction of insulin (130 mM Renaturation of reduced, denatured RNase A, which contains eight sulfhydryl groups, involves the oxidation of its thiol groups followed by rearrangement of the disulfides to the native conformation (with four disulfide bridges) (Anfinsen and Scheraga, 1975).…”
Section: Cyo1 Has Protein Zn-dependent Disulfide Isomerase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, DnaJ has been found to have thiol-disulfide oxidoreductase activity but little, if any, isomerase activity (14).…”
mentioning
confidence: 99%